Content Analysis of English Textbook Entitled â€œBahasa Inggris SMA/MA Kelas Xâ€ Published By Penerbit Yrama Widya. - Rasyid, Nirma Selastiana; Lio, Asrun; Rohmana, Rohmana (Universitas Halu Oleo, 2021)
Content analysis of the textbook has an important role because the analysis result can be used to determine whether the teacher can use the content of the textbook, or it needs to be revised. This research was conducted to analyze the content of English textbook based on five criteria proposed by Badan Standar Nasional Pendidikan (BSNP). This research used qualitative with descriptive method. The data were collected from an English textbook entitled Bahasa Inggris published by Penerbit Yrama Widya for Senior High School. The instrument of this research was a table checklist from BSNP. The researcher used the English textbook that has been applied in SMAN 1 Kapoiala as data sources. In collecting and analyzing the data, the researcher used a table checklist to find out the result of this research. Then, the researcher described the result of the table checklist regarding the completeness, in-depth, social function, element and structure of meaning, and linguistic features criteria. The result of this research showed that from nine chapters of this textbook, five chapters did not successfully fulfill five criteria from BSNP and four of them had successfully fulfilled. This research can be useful for teachers to gain information about the suitability of the content of the textbook following BSNP standard. It is also useful for the authors of the English textbook to improve the quality of the content of the textbook.